2021
DOI: 10.3892/mmr.2021.12048
|View full text |Cite
|
Sign up to set email alerts
|

Emerging landscape of circHIPK3 and its role in cancer and other diseases (Review)

Abstract: Circular RNAs (circRNAs) are a special class of recently re-discovered RNAs, which are covalently closed ring RNA molecules. circRNAs have been reported to possess multiple functions and are considered crucial regulators of several processes, and are therefore gaining increasing attention. In recent years, increasing evidence has shown that circRNAs are implicated in several crucial biological processes via regulation of gene expression, and their dysregulation is also associated with the development of numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…CircHIPK3 is a well-known circRNA involved in tumorigenesis. However, its expression is usually upregulated in different cancers [81]. In fact, two independent studies in glioma, another type of brain tumor [82,83], showed an overexpression of circHIPK3 and its involvement in the disease by reducing the expression of miR-421 and miR-124, which prevent cell proliferation and growth through CDK6 inhibition [84].…”
Section: Discussionmentioning
confidence: 99%
“…CircHIPK3 is a well-known circRNA involved in tumorigenesis. However, its expression is usually upregulated in different cancers [81]. In fact, two independent studies in glioma, another type of brain tumor [82,83], showed an overexpression of circHIPK3 and its involvement in the disease by reducing the expression of miR-421 and miR-124, which prevent cell proliferation and growth through CDK6 inhibition [84].…”
Section: Discussionmentioning
confidence: 99%
“…Although this provides more options for potential biological markers for cancer, it also creates difficulties in determining the application of a specific molecule. CircHIPK3 and circFOXO3 are two representative molecules that have been studied in a variety of tumors and other diseases ( 108 , 109 ). Unfortunately, the mechanism of action of both is still limited to miRNA sponge.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…CircHIPK3 functions as a scaffold for ELAV-like protein 1 (ELAVL1) and β-TrCP1 to enhance β-TrCP1-mediated ubiquitination and degradation of ELAVL1, leading to a decrease in the p21 level and cardiac senescence with a concordant increase in telomere length [145]. Studies suggest that circHIPK3 has a dual role in tumorigenesis and tumor progression [176][177][178]. Further studies are needed to delineate the circHIPK3-mediated regulation of β-TrCP1 activity over a diverse set of its substrates and their functional consequences in tumor development.…”
Section: Regulation Of β-Trcp Activity 61 Upstream Effectors Of β-Trc...mentioning
confidence: 99%